PENGARUH PROFITABILITAS, TRANSFER PRICING DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE - Ayu Sahyani Dewi; Anak Agung Ketut Agus Suardika (UNHI Press, 2021)
Optimizing the largest source of income for the state is very important in supporting government financing and national development. To support government financing and national development, which aims to improve the welfare of the community by exploringdomestic sources of funds, namely taxes. In order to minimize the tax burden, certain companies will usually try to reduce their tax costs in order to get higher profits. Companies will usually do a business by taking tax avoidance. This study aims to examine the effect of profitability, transfer pricing and institutional ownership on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2013 - 2019 with a population of 40 companies. Data is obtained by accessing the Indonesia Stock Exchange (BEI) page. Determination of the number of samples using purposive sampling method, in order to obtain a sample of 49 mining sector companies. Hypothesis testing is done by using multiple linear regression analysis techniques. In this study, the hypothesis testing method uses a significance level of 5%. The results showed that simultaneously, profitability, transfer pricing and institutional ownership have an effect on tax avoidance. Meanwhile, partially shows that the first result, namely the profitability variable has no significant effect on tax avoidance. The second result shows that the transfer pricing variable has no significant effect on tax avoidance. The third result shows that institutional ownership has a negative significant effect on tax avoidance.